2020
DOI: 10.1097/cm9.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides: bridging innate and adaptive immunity in the pathogenesis of psoriasis

Abstract: Antimicrobial peptides (AMPs) are small molecules produced by a myriad of cells and play important roles not only in protecting against infections and sustaining skin barrier homeostasis but also in contributing to immune dysregulation under pathological conditions. Recently, increasing evidence has indicated that AMPs, including cathelicidin (LL-37), human β-defensins, S100 proteins, lipocalin 2, and RNase 7, are highly expressed in psoriatic skin lesions. These peptides broadly regulate immunity by interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 137 publications
0
20
0
2
Order By: Relevance
“…Among these components, there are antimicrobial peptides (AMPs). As important components of the animal innate immune system, AMPs have a strong immunomodulatory and antimicrobial properties and are able to activate and modulate the adaptive immune responses ( Lai and Gallo, 2009 ; Donnarumma et al., 2016 ; Liang and Diana, 2020 ; Ma et al., 2020 ). Recent studies demonstrated that AMPs are involved in the regulation of mucin and TJs expression and microbiota composition ( Liévin-Le Moal and Servin, 2006 ; Muniz et al., 2012 ; Kiatsurayanon et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these components, there are antimicrobial peptides (AMPs). As important components of the animal innate immune system, AMPs have a strong immunomodulatory and antimicrobial properties and are able to activate and modulate the adaptive immune responses ( Lai and Gallo, 2009 ; Donnarumma et al., 2016 ; Liang and Diana, 2020 ; Ma et al., 2020 ). Recent studies demonstrated that AMPs are involved in the regulation of mucin and TJs expression and microbiota composition ( Liévin-Le Moal and Servin, 2006 ; Muniz et al., 2012 ; Kiatsurayanon et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The wide spectrum of defensin activity on immunocompetent cells, their selectivity and ability to shift the proinflammatory response to an antiinflammatory one have led to the assumption that the immunomodulatory activity of defensins is no less important than the antibacterial activity, and it serves as a key factor in the binding of the innate and adaptive immune response [ 136 , 189 , 190 ].…”
Section: Immunomodulatory Activity Of Ampsmentioning
confidence: 99%
“…However, in most cases, the initial activation of innate immunity leads to the breaking of tolerance and persistence of autoimmunity, as evidenced by the activation of T helper (Th) 1 and Th17 arms of the adaptive immune system and the accumulation of oligoclonal T cells secreting INF-È and Th17-signature cytokines in the lesional skin [23,24]. Initial immune events in psoriasis are triggered in response to endogenous danger signals released by keratinocytes following stress, infection or injury, of which cathelicidin, human β-defensin and S100 proteins have been most studied [25,26]. In a simplified version, these antimicrobial peptides (AMPs), along with other released cytokines and chemokines, promote activation of dendritic cells, which in turn have an inherited capacity to present autoantigens to naïve autoantigen-specific T-helper cells in the regional draining lymph nodes, leading to their activation and clonal expansion.…”
Section: Immunopathogenesis Of Psoriasis Vulgarismentioning
confidence: 99%